Effect of System Pressure and Solute Concentration on Fertilizer Injection Rate of a Venturi for Fertigation - Kumar, Mukesh; Rajput, T B S; Patel, Neelam (Journal of Agricultural Engineering, 2013)
Venturi injector is a commonly used device for fertilizer application through drip irrigation. The injection rate of a venturi injector mainly depends upon the suction created due to the difference between its upstream and downstream pressures. A commercially available venturi was evaluated for injection rate under the range of operating pressures from 1.0 to 2.0 kg.cm-2 using normal irrigation water and fertilizer solution. Maximum injection rate of the venturi with irrigation water was 106.4 l.h-1 at operating pressure of 2.0 kg.cm-2. Maximum injection rate (105.8 l.h-1), when urea fertilizer dissolved in irrigation water in the ratio of 0.25:1 (urea: water) was at the upstream and downstream pressure of 2.0 kg.cm-2 and 0.1 kg.cm-2, respectively. However, for muriate of potash (MOP) dissolved in irrigation water in the ratio of 1:1 (MOP: water), minimum injection rate of venturi was 1.44 l.h-1 at upstream pressure of 1.6 kg.cm-2 and downstream pressure of 0.5 kg.cm-2. Injection rate was observed to be inversely proportional to the concentration of the fertilizer solution. However, it was directly proportional to the pressure gradient i.e. decrease in pressure gradient across the venturi decreased the injection rat